Characterization of aroma-active compounds in steamed breads fermented with Chinese traditional sourdough. (December 2021) - Wang, Yuan-Hui; Yang, Yue-Ying; Li, Hao-Qi; Zhang, Qi-Dong; Xu, Fei; Li, Zhi-Jian
Abstract: The aroma components of Chinese sourdough steamed breads (CSSBs) play a vital role in CSSBs flavor. Fifteen aroma-active compounds of eight CSSBs fermented with sourdoughs from different regions were identified by gas chromatography-olfactometry and aroma extract dilution analysis. Odor activity values (OAVs) of ( E, E )-2, 4-decadienal, naphthalene, 1-pentanol, 1-heptanol, 2-pentylfuran, 1-octen-3-ol were high, and these compounds provided CSSBs with the green, floral, fruity, alcoholic, nutty, sweet, fatty and mushroom odor. The aroma properties of Nanyang and Weinan samples belonged to the same category, while Taian sample had unique odor. Moreover, Xi'an sample had a rich and distinct aroma, such as strong green, floral and fatty odor. In addition, the aroma profiles of CSSBs fermented by different types of sourdough (Lao-mian starter or Jiao-zi starter) were significantly different. The OAVs and concentrations of key aroma components in CSSBs from different origins were diverse, which made different CSSBs had their own unique aroma characteristics. Graphical abstract: Image 1 Highlights: Fifteen aroma compounds were identified in Chinese sourdough steamed breads (CSSBs). ( E, E )-2, 4-Decadienal, naphthalene, 1-pentanol, 1-heptanol and 2-pentylfuran had high OAVs. CSSBs had the aroma profile of green, floral, fruity, alcoholic, nutty and sweet. CSSBs (Xi'an) had a rich and distinct aroma (strong green, floral and fatty odor). Aroma of CSSBs fermented by "Lao-mian" was different from that fermented by "Jiao-zi".